Drosophila as a model to study cardiac aging - Nishimura, Mayuko (2010)
With age, cardiac performance declines progressively and the risk of heart disease, a primary cause of mortality, rises dramatically. As the elderly population continues to increase, it is critical to gain a better understanding of the genetic influences and modulatory factors that impact cardiac aging. In an attempt to determine the relevance and utility of the Drosophila heart in unraveling the genetic mechanisms underlying cardiac aging, a variety of heart performance assays have recently been developed to quantify Drosophila heart performance that permit the use of the fruit fly to investigate the heart’s decline with age. As for the human heart, Drosophila heart function also deteriorates with age. Notably, with progressive age the incidence of cardiac arrhythmias, myofibrillar disorganization and susceptibility to heart dysfunction and failure all increase significantly. We review here the evidence for an involvement of the insulin-TOR pathway, the K(ATP) channel subunit dSur, the KCNQ potassium channel, as well as Dystrophin and Myosin in fly cardiac aging, and discuss the utility of the Drosophila heart model for cardiac aging studies.